2022
DOI: 10.1002/bab.2382
|View full text |Cite
|
Sign up to set email alerts
|

The heat‐stable protein fraction from Opuntia ficus‐indica seeds exhibits an enzyme protective effect against thermal denaturation and an antibacterial activity

Abstract: Desiccation tolerance in developing seeds occurs through several mechanisms among which, a common group of proteins named dehydrins has received considerable attention. So far, there is no information dealing with the accumulation of dehydrins in seeds of Opuntia ficus‐indica. We have initiated here an extraction protocol based on two critical steps: heat and acid treatments, and the purity of this fraction was analyzed by FTIR spectroscopy. Western blot analysis of the heat‐stable protein fraction (HSF) revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The statistics of this analysis demonstrated that seed oil has no antibacterial action for Pseudomonas aeruginosa, while Staphylococcus aureus and Escherichia coli exhibited antibacterial properties [100]. The antimicrobial assays conducted in this study focused on specific bacterial strains, including Gram-negative bacteria such as Agrobacterium tumefaciens and Escherichia coli as well as Gram-positive bacteria like Micrococcus aureus, on 96-well microplates by the broth microdilution method for 24 h at 37 • C, inhibiting growth in minimum extract concentrations [101].…”
Section: Antibacterial Effectmentioning
confidence: 98%
“…The statistics of this analysis demonstrated that seed oil has no antibacterial action for Pseudomonas aeruginosa, while Staphylococcus aureus and Escherichia coli exhibited antibacterial properties [100]. The antimicrobial assays conducted in this study focused on specific bacterial strains, including Gram-negative bacteria such as Agrobacterium tumefaciens and Escherichia coli as well as Gram-positive bacteria like Micrococcus aureus, on 96-well microplates by the broth microdilution method for 24 h at 37 • C, inhibiting growth in minimum extract concentrations [101].…”
Section: Antibacterial Effectmentioning
confidence: 98%
“… Szabała (2023) also showed the cryoprotective activity of purified DHN24 in the enzymatic assay and inhibition of bacterial growth under DHN24 overexpression. Interestingly, wheat DHN-5 showed weaker LDH protective effects than the heat-stable protein fraction from Opuntia ficus-indica seeds ( Drira et al., 2013 ; Drira et al., 2023 ). Some vacuolar Ca 2+ -binding proteins also showed cryoprotective activity against LDH ( Osuda et al., 2021 ).…”
Section: Specific Functions Of Organellar Dehydrinsmentioning
confidence: 99%
“…At3g17210 encodes heat stable protein 1 (HS1) 4 . Such proteins harbor short chains of amino acids; thus, they maybe function as auxiliary proteins to exhibit enzyme protective effects against abiotic stress (Drira et al, 2023). In addition, under negative ionization mode, the metabolites 4-coumaric acid and LPC18:0 were in significantly negative correlations to H9X056 and H9VDW5 (Supplementary Figure S5D and the file "I_D.vs.NI_D_neg_I_D.vs.NI_D_cor" in Supplementary Table S16), suggesting that the enrichment of the two proteins might downregulate their levels.…”
Section: Serendipita Indica-induced Drought Tolerance By Improving Bi...mentioning
confidence: 99%